Finite Element Analysis on Knee Joint with Leg Length Inequality - Othman, N. F.; Suhaimi, M. N. A.; Basaruddin, K. S.; Som, M. H. Mat; Rusli, W. M. R. (International Journal of Engineering and Technology, 2018)
This study aims to investigate the effect of leg length discrepancy (LLD) on the joint reaction stress and strain of femur particularly in the knee joint. The knee joint model was developed using CATIA and imported into ANSYS to simulate the LLD case based on the value of the joint reaction force from the previous experimental study. The analysis was done under a linear static condition. The knee components were divided on three; bone (femur and tibia), cartilage (femoral cartilage and tibial plateau cartilage) and menisci. The effect of LLD on the knee joint was determined by observing the contour of equivalent stress and strain distribution on the knee joint components and the maximum equivalent von-Mises stress and strain. The result shows a higher value of stress and strain was found on the short leg compared to the long leg due to the LLD. The pattern of overall results shows that the magnitude of stress-strain is proportional to the level of increments in LLD. Since the short leg demonstrate the greater in stress and strain value, it is prone to experience failure in the future such as wear in cartilage.